UNDERSTANDING EMPLOYMENT CONSTRUCTS ACROSS BORDERS: A CROSS-NATIONAL COMPARISON OF MALAYSIA AND INDONESIA - Ling, Chow Poh; Teng, Phuah Kit (International Journal of Application on Economics and Business, 2025)
In today’s digital age, digital literacy has emerged as a vital skill that shapes employability and workforce preparedness. The research examines the impact of digital literacy on employability among employees in Malaysia and Indonesia through a quantitative methodology and purposive sampling. Data were collected from 469 participants (238 Malaysians and 231 Indonesians) via structured questionnaires. Results show that nationality does not significantly moderate the link between digital literacy and employability, suggesting that perceptions of these constructs are consistent in both countries. This finding implies that initiatives to improve digital literacy can be applied similarly across these contexts. The study highlight the consistent relationship between digital literacy, employability, and related factors such as media literacy and perceived ease of use across different nationalities. For managers, policymakers, educators, and corporate trainers, this suggests that standardized frameworks may be effective in fostering digital skills and employability, supporting a cohesive regional strategy.